Deformation twinning in single-crystal Mg under high strain rate tensile loading: A time-resolved X-ray diffraction study. (15th April 2022) - Li, Yuxiao; Huang, Jiawei; Fan, Duan; Lu, Lei; Zhang, Bingbing; Zhong, Tao; Dai, Bo; Zhang, Siwei; Tao, Ye; Zhang, Yiyang; Chen, Sen; Luo, Sheng-Nian
Abstract: We investigate deformation twinning in single-crystal Mg with in situ, time-resolved ( μ s-scale), synchrotron X-ray diffraction under high strain rate split Hopkinson tension bar loading. Extension twinning occurs upon dynamic tension along 〈 0001 〉, but is absent upon tension along 〈 11 2 ̄ 0 〉 . Such deformation anisotropy is a result of the unipolarity of deformation twinning which depends on directionality and resolved shear stress. The twinning mechanism is common for pure Mg in a wide range of strain rates and different loading conditions (one-dimensional stress and one-dimensional strain). Graphical abstract: Highlights: First in situ XRD study on single-crystal Mg under high strain rate tensile loading. Deformation is extension twinning-dominated for high strain rate tensile loading along 〈 0001 〉 . Deformation is slip-dominated for high strain rate tensile loading along 〈 11 2 ̄ 0 〉 . Deformation anisotropy is common across different strain rates/stress conditions. Deformation anisotropy is common across dynamic compression/tension, and shock release.